Recent applications of carbon-based composites in defence industry: a review - Harussani, M.M.; Sapuan, S.M.; Nadeem, Gohar; Rafin, Tahrim; Kirubaanand, W. (KeAi Communications, 2022)
Carbon-based composites, including carbon reinforced composites and carbon-matrix composites, in defence technologies have raised a lot of attention due to its significant physical capabilities, superior thermal and mechanical stability, and its eco-friendly nature. Carbon-based composite which incorporating with various carbonaceous materials such as coke, char, black carbon, activated carbon, carbon fibre and other carbon nanomaterials (carbon nanotubes, carbon nanofibres, graphene and graphite) are the greatest viable option for the development of advanced defence technologies. In this review article the characteristics of carbon-based materials and its composites are discussed for their distinct application in defence sectors; aeronautics, maritime, automotive, electronics, energy storage, electromagnetic interference (EMI) shielding and structures. The origin of carbonaceous materials and its production techniques were discussed. Carbon-based composites have a promising future in defence technology, particularly in chemical sensors, drug delivery agents, radar technologies, and nanocomposites due to their low cost, easy availability, flexibility in design and processing.